Polycystic Kidney Disease with Breast Nodules in a Male: A Case Report - Horyono, Caitlyn Natasha; Borries Foresto Buharman (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Polycystic kidney disease is a multisystem and progressive congenital kidney disorder characterized by kidney enlargement and the growth of cysts in the kidneys and other organs. Autosomal dominant polycystic kidney disease (ADPKD) is the most common type of inherited kidney disorder and is observed in 1/500 – 1/1000 people. The diagnosis is usually made by a positive family history , and the Ravine ultrasonographic criteria assess the age and number of cysts in both kidneys. Case presentation: A 37-year-old male was reported with complaints of intermittent hematuria and a painless lump in the right breast for the last 6 years. Patients routinely drink herbal medicine when symptoms appear. Abdominal physical examination revealed renal ballottement. The lump in the right breast is palpable as a lump ± 1 cm from the nipple. No abnormalities in kidney or liver function were found on laboratory examination. Ultrasound was performed, and polycystic kidney disease was obtained in both kidneys and liver, as well as a hypervascular solid nodule in the right breast. The patient was given antibiotics and antifibrinolytics. Healthy lifestyle education is also provided to patients. The patient was then referred for a biopsy of the nodule. Conclusion: Autosomal dominant polycystic kidney disease (ADPKD) is a common disease but only a few cases of ADPKD are accompanied by nodules in the breast, so a further approach is needed.